2007
DOI: 10.1149/1.2794672
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Reconstruction of Porous LSCF Cathodes

Abstract: In this initial study the electrochemically active region of a La 0.8 Sr 0.2 Co 0.2 Fe 0.8 O 3−␦ ͑LSCF͒ cathode was reconstructed in three dimensions using a focused ion beam/scanning electron microscope. The reconstructed volume totaled 1065 m 3 from the free air surface to the dense yttria-stabilized zirconia electrolyte interface. Various microstructural properties were measured, including overall porosity, closed porosity, graded porosity, surface area, tortuosity, triple-phase boundary length, and pore si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(172 citation statements)
references
References 27 publications
2
166
2
2
Order By: Relevance
“…2) The MATLAB application TauFactor uses an iterative over-relaxation method to solve the diffusion equation and, again, compares the flux through the porous phase to the flux through the dense volume of equal dimensions Brown et al, 2016b;Finegan et al, 2016). 3) The pore centroid method calculates the path length through a porous structure by following the centre of mass of pores of each 2D image slice along the in-plane direction of the volume and dividing it by the thickness of the volume (Gostovic et al, 2007;Smith et al, 2009;Shearing et al, 2012;Cooper et al, 2013;Cooper et al, 2014). 4) The fast marching method calculates the shortest path through the analysed phase by creating a distance map between the starting and end boundary of a propagating front.…”
Section: Image-based Tortuosity Calculation Approachesmentioning
confidence: 99%
“…2) The MATLAB application TauFactor uses an iterative over-relaxation method to solve the diffusion equation and, again, compares the flux through the porous phase to the flux through the dense volume of equal dimensions Brown et al, 2016b;Finegan et al, 2016). 3) The pore centroid method calculates the path length through a porous structure by following the centre of mass of pores of each 2D image slice along the in-plane direction of the volume and dividing it by the thickness of the volume (Gostovic et al, 2007;Smith et al, 2009;Shearing et al, 2012;Cooper et al, 2013;Cooper et al, 2014). 4) The fast marching method calculates the shortest path through the analysed phase by creating a distance map between the starting and end boundary of a propagating front.…”
Section: Image-based Tortuosity Calculation Approachesmentioning
confidence: 99%
“…Berson et al [16] reported that Bruggeman correction, which was only valid for ε 0.6  , introduced big errors in low [15,[19][20][21][22][23][24][25][26][27], line + solid triangle symbols denote the results calculated by Equation (9), solid square symbols denote the results calculated by the 3D sphere packing model [17]. Figure 4 shows the dependence of fpε, τqp" D eff {D 0 q on porosity.…”
Section: Resultsmentioning
confidence: 99%
“…LSCF has found its application as oxygen membrane [1][2][3][4], catalyst for combustion and oxidative coupling of hydrocarbons [5][6][7], and electrocatalyst for redox reactions in solid oxide fuel cells (SOFCs) [8][9][10][11][12]. LSCF as an electrode for SOFC exhibits high mixed electronic-ionic conductivity, high thermal and chemical stability, and also compatibility with other fuel cell materials.…”
Section: Open Accessmentioning
confidence: 99%